ACHIEVEMENT STUDENT DECISION MAKING SYSTEM USING ANALYTIC HIERARCHY PROCES (AHP) METHOD IN BINA DHARMA PRINGSEWU LKP - Nurul Hakim, Ambar; Wati, Rina (YHMM PUBLISHING, 2023)
Learning achievement is an illustration of the level of success of students in learning. In accordance with the regulations determined by the Bina Dharma Pringsewu Training Course Institution (LKP) to find out outstanding students, criteria are needed to determine who will be selected as the most accomplished students. The purpose of this study is to design a Student Value Information System as a support in decision making and daily operational needs, and to compare the effectiveness and efficiency of processing data processing and the presentation of information between existing systems and information systems that will be proposed. In improving the development process, the writer will develop a Student Information System as a support in making decisions using Visual Basic 6.0 programming language and using the Analytic Hierarchy Process (AHP) method. The AHP (Analytic Hierarchy Proces) method is suitable to be applied by determining the weight value of all criteria for each student so that the school can make a decision to determine the outstanding students. The research carried out in this case is a qualitative descriptive study by conducting a survey of the object of research, namely at the Institute of Training Courses (LKP) Bina Dharma Pringsewu, Pringsewu Regency using data collection techniques namely observation (observation), interview (interview), and library research. The conclusion of this research is that the new system is expected to provide convenience to the parties involved in processing data quickly and accurately and can store data safely so that it helps in the process of service to students and the public